IMPLEMENTASI SUPERVISI PENDIDIKAN DALAM MENINGKATKAN MUTU GURU DI MTS. SUNAN AMPEL KAMAL KUNING, KREJENGAN - Nafisatul Kamila; Zainul Firdaus (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This analysis was conducted to pay attention to how important school principals are in improving the performance of educators, in terms of controlling and evaluating the institutions they lead. By making and creating good and certainly professional working conditions, it is necessary to have supervision and innovation in managing schools. By rethinking the ideas to be implemented in schools and setting targets to be achieved in the future, in order to promote and succeed in schools to produce better and quality human resources. In the leadership of the school principal, instructions, encouragement, and appreciation are needed for educators in carrying out their duties with full responsibility. The purpose of this study intends to find out the application of supervision carried out by the principal in improving teacher performance and competency at MTs Sunan Ampel, Kamal Kuning, Krejengan and also to find out more about the performance of teaching staff after carrying out evaluations regarding the learning process at MTs Sunan Ampel , Kamal Kuning, Krejengan. This type of research method is qualitative. Qualitative is research that is based on qualitative data to answer research questions. Qualitative research is research that gives meaning or in other words interprets individual actions or reactions in the substance of teaching staff by using methods or methods of observation, interviews, and documentation. The results of this study are the application of supervision, in improving the performance of educators, coaching programs are needed to support so that performance remains good and lagging behind, such as attending seminars, exchanging educational staff, attending training, etc. As well as evaluation which is very important in improving the quality of schools starting from the education staff with the annual work meeting and checklist of teacher data completeness.